DNA extraction from strawberry (Fragaria ananassa) as a practical tool for teaching genetic content - Andrade, Beatriz Santana de; Dias, Bryan Teixeira Coelho; Silva, Elen Cristina Soares da; Santos, Gabriela Thaís Boaventura; Lopes, Jeyson Césary (Seven Editora, 2024)
Genetics is an important curricular component of the Biological Sciences discipline and a great study tool for scientists. The aim of this study was to verify the existence of DNA molecules in strawberry. To carry out the practice, DNA extraction was performed from the strawberry. A tangle of white strands can be seen between the solution and the alcohol, forming a 3-phase mixture. It can be concluded that DNA extraction from the strawberry is an easy practice to perform. DOI:https://doi.org/10.56238/sevened2024.010-044